A STUDY ON BANK EMPLOYEES’ EFFICIENCY TOWARDS INTERNET BANKING (International Journal of Food and Nutritional Sciences, 2023)
Before the advent of computerised banking, the manual system of recording, storing, and retrieving financial data was in use. As the winds of change began to blow, the vast majority of banks, if not all, switched to using electronic banking (e-banking) for transactions. Currently, e-banking is quickly replacing traditional banking as the standard in India. Numerous compelling arguments have been presented in favour of this dynamic transformation in financial systems. One of them is the inherent advantage of e-banking, which encourages time savings and incredibly high levels of efficiency of bank employees in the speed at which financial activities are carried out, so improving the performance of banks. The correctness and dependability of this information are also benefits if exact facts are entered